Shipping oil from the Russian Arctic: Past experiences and future prospects - Bambulyak, Alexei; Sydnes, Are K.; Milakovic, Aleksandar-Sasa; Frantzen, Bjørn (2015)
Transport of oil from Russian Arctic ports to Western markets was insignificant prior to 2002. In 2002, there was a major surge, with 5 million tonnes delivered westwards through the Barents Sea. By 2004, this had increased to 12 million tonnes. Since then, annual volumes have been on levels between 9 and 15 million tonnes. In the near future, the flow of oil cargo in the Arctic may rise significantly, as a result of the development of oil and gas fields and port capacities in the North. Oil offloading terminals in the Russian Arctic have been developed and overall shipping capacity has been enlarged, though each terminal has its history of ups and downs. Various logistic schemes have been developed for shipping oil and gas produced in the Northern regions and bringing petroleum cargo to the Arctic coast over long distances using pipelines, railways and river ships. In this paper, we present an overview of experiences with transport schemes at onshore and offshore terminals along the Russian Arctic coast and indicate the prospects for future oil and gas shipping in the North. We examine logistic solutions that reflect Arctic shipping challenges, and pay attention to oil pollution prevention and response systems. We find that logistics solutions are more varied, flexible and complex than often assumed, and that estimates of potential cargo and terminal capacity will need to reflect oil and gas production beyond the Arctic regions. Finally, we note the trend towards greater centralisation of terminal and oil-spill response capacity during the last 15 years.